Who Keeps the Score on the London Stages? - Stefanova, Kalina (Taylor and Francis, 2013)
How does one become a theater critic in London? What do the theater critics think of their profession? How are they judged by those they critique? What do both critics and theatre-makers think of their mutual object of desire - the British Theatre?Who Keeps the Score on the London Stages? sets out to find the answers to these questions and many more in this long overdue publication on Britain's current theatre scene. Included are comprehensive interviews with more than fifty major London theatre critics and theater-makers, including Sir Alan Ayckbourn, Stephen Ber.